Hereditary Fructose Intolerance - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Symptoms of neurological impairment in five children with hereditary fructose intolerance are described from the Service de Pediatrie, Hopital Antoine Beclere, Clamart, France.